Complete mitochondrial genome and phylogenetic analysis of Ixodes acutitarsus (Acari: Ixodidae). Issue 6 (3rd June 2022) - Lu, Xinyan; Jiang, Dandan; Du, Chunhong; Rao, Caihong; Yin, Jianqiang; Fang, Yihao; Yang, Xing
Abstract: Ixodes acutitarsus is regarded as the largest Ixodes tick around the world. I. acutitarsus is capable to transmit a wide range of animal and human pathogens. This research pioneered sequencing of the complete mitochondrial genome of I. acutitarsus . With a length of 14, 475 bp, the complete mitochondrial genome encodes 13 protein-coding genes (PCGs), two ribosomal RNA genes (rRNAs), 22 transfer RNA genes (tRNAs), and one replication-initiating region. The phylogenetic relationship was established using the Maximum-likelihood method to indicate that I. acutitarsus and the others of the genus Ixodes fit into the same branch, which confirms the inclusion of I. acutitarsus in the genus Ixodes. The complete mitogenome of sequenced I. acutitarsus provides molecular evidence for the taxonomic status and phylogenetic position of several Ixodes species.